Noise-powered probabilistic concentration of phase information - Usuga, Mario A.; Müller, Christian; Wittmann, Christoffer; Marek, Petr; Filip, Radim; Marquardt, Christoph; Leuchs, Gerd; Andersen, Ulrik L. (Nature Physics, 2010)
Phase-insensitive optical amplification of an unknown quantum state is known to be a fundamentally noisy operation that inevitably adds noise to the amplified state. However, this fundamental noise penalty in amplification can be circumvented by resorting to a probabilistic scheme as recently proposed and demonstrated in refs 6, 7, 8. These amplifiers are based on highly non-classical resources in a complex interferometer. Here we demonstrate a probabilistic quantum amplifier beating the fundamental quantum limit using a thermal-noise source and a photon-number-subtraction scheme. The experiment shows, surprisingly, that the addition of incoherent noise leads to a noiselessly amplified output state with a phase uncertainty below the uncertainty of the state before amplification. This amplifier might become a valuable quantum tool in future quantum metrological schemes and quantum communication protocols. © 2010 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2022-06-05